2003
DOI: 10.1097/01.brs.0000099114.40764.46
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Tuberculomas in the Brain and Spinal Cord: A Case Report

Abstract: Our experience indicates that antituberculous medication is effective in managing multiple central nervous system tuberculomas. The purpose of surgical intervention is to decompress the cord or brain when progressing neurologic defects occur and to examine the tissue pathologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 21 publications
2
50
0
Order By: Relevance
“…Arseni and Samtica found only five intramedullary tuberculomas in their series of 210 cases of CNS tuberculosis 2) . Concurrent intramedullary and intracranial tuberculomas are very rare and only 5 cases has been Disseminated Tuberculoma in Spinal Cord and Brain|HS Park, et al reported so far 6,13,19,21,23) . Thacker and Puri 21) reported a 6-year-old girl who presented with progressive paraparesis in whom imaging revealed intramedullary tuberculoma with incidentally discovered multiple intracranial tuberculoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Arseni and Samtica found only five intramedullary tuberculomas in their series of 210 cases of CNS tuberculosis 2) . Concurrent intramedullary and intracranial tuberculomas are very rare and only 5 cases has been Disseminated Tuberculoma in Spinal Cord and Brain|HS Park, et al reported so far 6,13,19,21,23) . Thacker and Puri 21) reported a 6-year-old girl who presented with progressive paraparesis in whom imaging revealed intramedullary tuberculoma with incidentally discovered multiple intracranial tuberculoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thacker and Puri 21) reported a 6-year-old girl who presented with progressive paraparesis in whom imaging revealed intramedullary tuberculoma with incidentally discovered multiple intracranial tuberculoma. Yen et al 23) re-ported a 67-year-old man with known pulmonary tuberculosis who developed symptoms of spinal cord compression. Imaging revealed an intramedullary tuberculoma along with multiple intracranial tuberculomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 IMT occurs rarely and usually presents with progressive compressive myelopathy. 8,9 If patients can be diagnosed in the early stage and treated properly, they are expected to have excellent neural recovery. 10 Gadolinium-enhanced MRI is considered to be the diagnostic tool of choice in patients with ongoing inflammation.…”
Section: Discussionmentioning
confidence: 99%